1999
DOI: 10.1006/bcmd.1999.0237
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Numbers Relate to Bone Involvement in Gaucher Disease

Abstract: ABSTRACT:The major elements of bone pathology in Gaucher disease are a failure of osteoclast and osteoblast function, resulting in osteopenia and also osteonecrosis. T lymphocytes have recently been found to be involved in the regulation of osteoblast/osteoclast activity in vitro. In the present report the peripheral blood T major lymphocyte subsets were investigated in a group of genotyped type 1 Gaucher disease patients. A total of 31 patients were studied: 21 non-splenectomized (5 N370S homozygotes) and 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
2
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 29 publications
(22 reference statements)
2
36
2
5
Order By: Relevance
“…We did not find disturbed absolute CD8+ cell counts, either in patients with or in those without bone involvement. This finding argues with what other studies have reported, namely, that GD patients with bone involvement have reduced absolute CD8 + cell counts (Lacerda et al 1999). This discrepancy might be attributed to the relatively small number of osteopathic patients included in our study (n ¼ 5).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We did not find disturbed absolute CD8+ cell counts, either in patients with or in those without bone involvement. This finding argues with what other studies have reported, namely, that GD patients with bone involvement have reduced absolute CD8 + cell counts (Lacerda et al 1999). This discrepancy might be attributed to the relatively small number of osteopathic patients included in our study (n ¼ 5).…”
Section: Discussionsupporting
confidence: 88%
“…Among few studies, Balreira et al (2005) demonstrated that patients, either under enzyme replacement therapy (ERT) or not, have decreased proportion of CD4+ cells and increased proportion of CD8+ cells. Lacerda et al (1999), however, found that both CD4+ and CD8+ absolute numbers were decreased in patients with bone manifestations. Moreover, Burstein et al (1987) reported decreased number of NKT cells, whereas Braudeau et al (2013) demonstrated that untreated patients exhibit low NK, T gd2 , and naive CD4+ cells and high CD4+ memory T-cell counts.…”
Section: Introductionmentioning
confidence: 86%
“…Of particular relevance to the process of FL transformation is whether the transformed lymphoma arises directly from FL, or might arise from additional genetic events in a lymphoma progenitor cell. Such a model is supported in findings by Carlotti et al 4 and those of Ruminy et al 5 wherein intraclonal diversity, as defined by the patterns of somatic hypermutation occurring in FL and transformed lymphoma, is more complex than previously described.…”
supporting
confidence: 55%
“…on March 28, 2019. by guest www.bloodjournal.org From bone involvement, but it is uncertain whether this is a primary or secondary phenomenon. 4 Adipocytes are significant players in bone metabolism, but little is known about the interactions between Gaucher cells and fat cells and how they might influence bone mineralization. Altered glucose metabolism, insulin resistance, and abnormal adiponectin levels that may affect bone mineralization have been reported in untreated GD1 patients, but their clinical importance is unclear.…”
Section: O C T O B E R 2 0 0 9 I V O L U M E 1 1 4 N U M B E R 1 mentioning
confidence: 99%
“…The involvement of immune cells has been implicated, but the underlying molecular defect is poorly understood (6)(7)(8)(9). For example, GD has been associated with impaired host-defense against microbial infections (10,11), up-regulation of T-helper (Th)1 and Th2 cytokines (6,12,13), dysfunction of monocytes (14), and an increased risk for lymphoid malignancies, most strikingly for multiple myeloma (15)(16)(17)(18).…”
mentioning
confidence: 99%